EUROMOD and the Development of EU Social Policy - Anthony B. Atkinson (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
The purpose of this paper is to set EUROMOD – the EU-wide tax and benefit model - in the context of the development of EU social policy. It explores the relation between the rapidly evolving EU social inclusion process and investment in European social science infrastructure. In so doing, I look mainly to the future, but I would like to begin in Sections 1 and 2 with the historical background. It is only in this way that we can place in context the achievements of EU social policy and understand the need for further development. I then describe in Section 3 the main elements of the EU Social Inclusion process and the National Action Plans of Member States. A key role is played by the social indicators agreed at Laeken in 2001, which are the subject of Section 4. Looking to the future, the monitoring of performance by means of social indicators may lead to the setting of targets (Section 5). All of this relates to process and analysis, but substantive progress requires policy innovation and policy learning. In Section 6, I begin with the assessment of policy at the national level, arguing that there is a role for EUROMOD in analysing the policies of individual Member States on a consistent basis across the EU. The role is clearly crucial at the EU level (Section 7). The potential for policy assessment is demonstrated in Section 8 in the context of a ?new intergenerational pact?, and in terms of working back from possible targets in Section 9. The main lessons for policy analysis are summarised in Section 10.
Keywords: 330